Addressing Sexual Offences in South Africa: Moving Past Rhetoric and Empty Gestures - Stander, Abigail (Department of Public Law, 2022)
There is a plague of sexual violence in South Africa. As a country dedicated to the rights to life, dignity, bodily integrity, privacy and the right to be free from all forms of violence, it is the government's duty to adequately address the rate of sexual offences in the country. The government has not been silent on this issue, but its response beyond issuing strong statements accompanied by long sentences for the few offenders convicted, is lacking. Some important legislative changes have been brought about in the SORMA but without widespread change of social attitudes these improvements are going to have very limited impact. This paper explores why South Africa's current approach towards sexual offences is inadequate and how it should be improved. The first section lays out the background and development of South Africa's sexual offence laws (and laws relating thereto). The myths and stereotypes about sexual offences and their victims that prevailed in our legal system for decades, still persist in the minds of many police and judicial officers today. This has negatively affected how sexual offences are policed in the country. It begs the question of whether victims should be afforded specific rights in sexual offence cases. This section also discusses how mandatory minimum sentences came about as a response to rising crime rates. While the changes to the law have been praised for being more progressive for victims of sexual offences, its actual impact will remain insignificant until procedures for obtaining justice for victims are improved. The next section critiques the current legal framework relating to sexual offences, namely, the SORMA and the Criminal Law Amendment Act 105 of 1997. Legislative changes such as the new definition of rape and the formal acknowledgment of sexual offences courts are promising. However, the establishment of the National Register for Sexual Offenders and the mandatory minimum sentences for rape were poorly researched solutions. This paper argues that since SORMA's approach has not improved the experience of victims in the past 13 years, either duties for police officers in sexual offence cases should be legislated or victims should be afforded specific procedural rights. The final section of this paper discusses feasible options for South Africa to address sexual offences. The first is in the form of structured sentencing guidelines to steer the discretion given to judges in handing down sentences. The second is in the form of prevention strategies. This paper highlights how important it is for the government to start to implement policies that will address the societal norms that allow sexual violence to flourish. The government's only solution cannot be to keep clutching at popular mandatory sentencing. They owe it to the citizens of South Africa to commit to long-term social change initiatives.